A pavilion for Constantin Meunier by architect Gaston Eysselinck (1929) - Marc Dubois (VLC Arquitectura)
At the end of the 19th century, the Belgian sculptor Constantin Meunier (1831-1905) had an international reputation. The main theme of his oeuvre is the working class. His sculptures were frequently exposed in different European cities. Two of his works were presented at the art biennale of Venice in 1907. The Ny Carlsberg Glytotek in Copenhagen possesses the largest collection of Meunier’s sculptures (48 pieces). In 1929, the S.C.A.B. (Société Centrale d’Architecture de Belgique), the national architects organisation, launched a competition for the "Monument au Travail", a monument that puts four reliefs and five sculptures together in Laken (Brussels). The architect Mario Knauer (1879-1948) was chosen to build the monument. The young architect Gaston Eysselinck (1907-1953) participated with a fascinating project, but was directly eliminated by the jury. What were the ideas of Eysselinck’s proposition? A pavilion with a roof garden and an open ceiling? A meditation space where the light enters, following the example of Dante’s Paradise? Or was he influenced by the German pavilion of Mies van der Rohe in Barcelona, built in the beginning of 1929?